Cross-Cultural Supervision Amidst A Generational Shift - Dymitrow, Mirek (Journal of Education Culture and Society, 2022)
Aim. This paper sets out to draw on my experience as a Sweden-based academic supervisor who is also active in Poland to reflect on the issue of cross-cultural supervision amidst a presumed generational shift that goes on in Poland. Split between stories of a destructive hierarchy and non-transparency in Polish academia on the one hand, and of an emergent “West-minded” reorientation on the other, this paper looks into the cultural idiosyncrasies that have made supervision in Poland tricky for me, if not outright difficult. Methods. This paper focuses on the perspectives of ten active PhD supervisors based in Poland. Using questionnaires and interviews the respondents were asked to reflect upon whether a generational shift is underway. This was done by comparing the ideals, attitudes, and behaviours of their past supervisors to those of their own. The results were then analysed through a set of challenges common in cross-cultural supervision and compared to the Swedish context. Results. The findings point to a possible gap between self-assessment of the respondents as progressive and the regressive practices that seem to linger and impact the students. Conclusion. A tentative conclusion is that the long-awaited generational shift in Poland has not yet fully taken root. This is further reflected in how markedly different the culture of supervision in Poland still is from the culture practised in Sweden. Cognitive value. The paper points to the difficulty of breaking free from the routines inherited from one’s past-generation supervisors. It also emphasises the benefits of cross-cultural supervision, given that shifts within cultural practices are difficult to perceive and implement while operating within a single cultural ecosystem.